Parahydrophobicity and stick-slip wetting dynamics of vertically aligned carbon nanotube forests. (November 2019) - Zhou, Ziyu; Gao, Tongchuan; McCarthy, Sean; Kozbial, Andrew; Tan, Susheng; Pekker, David; Li, Lei; Leu, Paul W.
Abstract: We report for the first time on the parahydrophobicity and stick-slip wetting dynamics of vertically aligned carbon-nanotube (CNT) forests and compare it with previously observed droplet infiltration characteristics. CNT surfaces have generally been reported to be superhydrophobic, but unstable, as the water rapidly infiltrates the forest. In this paper, we demonstrate the first observation of parahydrophobicity of CNT forests, where the surface exhibits an apparent static water contact angle close to 150° but may be turned upside down without the droplet rolling off. Evaporation plays a critical role in the dynamic wetting behavior of these high-density samples as water droplets are stable in moisture-saturated environments. The wetting dynamics in the ambient is driven by evaporation as opposed to infiltration and characterized by contact line pinning from the strong adhesive forces in the CNTs. The pinning force at the contact line gradually increases as the droplet evaporates until a critical force is reached, where the contact line suddenly jumps radially inward with a concomitant deflection of CNTs inward. We observe that taller CNT forests have a higher critical force for deflection and coalesce into cellular patterns with larger cell size, which both suggest that taller CNTs have stronger mechanical interactions with each other. Graphical abstract: Image 1